SUPREMASI HUKUM DALAM PERSPEKTIF FILOSOFI, SOSIAL, POLITIK UNTUK INDONESIA ADIL MAKMUR - Ardhani, Hasbi; Basriadi, Basriadi; Hamroni, Hamroni (STIS Darussalam Bermi, 2023)
This writing aims to analyze the cencept of the rule of law in perspective philosopical, social, and political for a just and prosperous Indonesia through inspection and rearrangement of laws and regulations to create order laws and regulations be taking into account the general principles and hierarchy of invitation, reforming the legal structure through institusional strengthening with increase the profesionalism of law enforcers. The research method used in this writing is a descriptive study that describes the rule of law in a philosopical, social, and political perspective for Indonesia fair prosperous. The rule of law philosopically, the law must be in accordance with the system, theory, principles, functions and objectives of law. The sosiological aspect of the law emerged from the aspirations of the community so that it is accepted and obeyed by the community. Meanwhile, from a political perspective, the law must be made by the goverment an independent state and not a colonial legacy.